SISTEM PENGOLAHAN DATA NILAI MATA KULIAH PADA PROGRAM STUDI TEKNIK INFORMATIKA UNIVERSITAS SAHID SURAKARTA - Mahardika Adiyanto; Astri Charolina (Universitas Sahid Surakarta, 2014)
College student outcomes assessment in education is, one very important factor, because with the assessment results of the course you will see clearly the level ofsuccess of an education provider (University) in educating students. The existence of the course assessment results will also provide a clear picture of college studentachievement outcomes, either individually or thorough.Assessment results, especially college students study programs in informatics at Sahid University of Surakarta already using a system based on a Local Area Network(LAN), but in this system there are still some shortcomings, the value of which can only be accessed within the campus, so the students when they want to see should come to campus. Troubleshooting solutions of these cases is the development of Information Systems Subjects Value Engineering Program Informaion At Sahid University of Surakarta web based. The existence of this system, is expected to renew the old system to the new system, so the data processing student grades will be faster and moreaccurate. In addition, the student information system can easily access the information value of the lectures from anywhere and anytime using the internet facilities